Pengembangan Organisasi di Fakultas Ilmu Kelautan dan Perikanan Universitas Maritim Raja Ali Haji - Priandika, Icip; Anjodah, Novechi; Istikhamah, Istikhamah (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2014)
This paper examines the dimensions of organizational development and the various dynamics at theFaculty of Marine Science and Fisheries (FIKP) Universitas Maritim Raja Ali Haji (UMRAH).Organizations that are not sensitive to changes in organizations that are dying, because in principle theorganization is a dynamic environment that demands for change is a necessity. This demand is noexception to the organization in the form of educational institutions which will be examined in thisstudy that FIKP. As an organization that is engaged in the provision of care and education services,changes in the environment have a great influence on FIKP Umrah, both internally and externally. Sothis study intends to explore how organizational development model in FIKP UMRAH?. The presenceof the high dependence of the above organization -in an effort pengembangan- the university. Programsand activities in developing the organization often collide by response duration of the university, whichmakes the process of developing a FIKP organization in the slower, so FIKP difficult to cope with thedemands of the changing environment.